Logarithmic STDM watermarking using visual saliency‐based JND model. Issue 10 (1st May 2015) - Wan, Wenbo; Liu, Ju; Sun, Jiande; Ge, Chuan; Nie, Xiushan
Abstract : Owing to the validity of measuring the visual visibility for image distortion, just noticeable distortion (JND) has been widely used in the quantisation‐based watermarking framework. However, the existing JND model treats every region in the image with an equal attention level. Visual saliency, which reflects the visual attention, is proposed to improve the perceptual JND model. Based on the improved model, a logarithmic spread transform dither modulation (STDM) watermarking scheme is proposed. Simulations show that the proposed watermarking scheme with the improved JND model has superior robustness compared with existing STDM schemes.